(untitled) ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2024)
This article provides a detailed exploration of the types of syntactic relations in a sentence, offering insights into their roles and importance in sentence structure. It categorizes syntactic relations into key types: subject-predicate, modification, complementation, coordination, subordination, agreement, and government. Each category is explained with clear definitions and examples, making the content accessible for linguists, students, and language enthusiasts. The two conclusions emphasize the importance of understanding these relations for effective communication, linguistic analysis, and appreciation of language’s structural complexity. This piece serves as a foundational guide for anyone seeking to deepen their knowledge of syntax and grammar.